[tex]\log_2(5x - 2) - \log_2 x - \log_2(x - 1) = 2[/tex]
[tex]\log_2 ( \frac{5x - 2}{x(x-1)} ) = 2[/tex]
[tex]\log_2 ( \frac{5x - 2}{x(x-1)} ) = \log_2 4[/tex]
[tex]\frac{5x - 2}{x(x-1)} = 4[/tex]
[tex]5x - 2 = 4x(x - 1)[/tex]
[tex]5x - 2 = 4x^2 - 4x[/tex]
[tex]0 = 4x^2 - 9x + 2[/tex]
[tex]0 = (4x - 1)(x - 2)[/tex]
[tex]\implies x = 2 \text{ or } x = \frac{1}{4} [/tex]
By putting one quarter into the equation we can see that it cannot work in any way involving real numbers as [tex]\log_2 ( \frac{1}{4} - 1) [/tex] would be log of a negative number, so x = 2.